Management of hypertension in the hemodialysis population: a review of the literature - Nabela Enam; Kavita Kakkad; Akshay Amin; Carole Lever (Greater Baltimore Medical Center, 2014)
Objective: The objective of this paper was to propose an algorithm for approaching hypertensive hemodialysis patients admitted to the hospital for hypertensive urgency. Methods: A literature search was conducted using PubMed (Medline). Articles selected were limited to humans and the English language. Results: We identified eight management modalities including: short-daily and nocturnal dialysis, sodium restriction, sodium profiling, antihypertensive medications, sympathetic denervation, bilateral nephrectomy, and bioimpedance spectroscopy. The benefits and drawbacks of each were investigated and discussed before implementation into the algorithm. Discussion: The algorithm presented suggests a linear approach to patient care, but treatment modalities may not be mutually exclusive, and additional factors, such as patient compliance and individual health status, should be taken into account to provide patients with optimum care.